A Geographical Analysis of Ruandz River Water Pollution - Khurshid, Asst.L.Media Asad; کەلێتەیی, م. م. مصطفى يوسف محمد كليتايي; قادر, م. م. دیدار حمد قادر; شیخ, م.م. مؤید شوکت شیخ (Sulaimani Journal for Humanities, 2025)
Water pollution is one of the most common global problems, and the Kurdistan Region is no exception. Therefore, this study focuses on the geographical analysis of water pollution in the Ruandz River. The primary aim is to highlight the extent of water pollution affecting the river. The methodology employed includes a private-to-general inference approach, quantitative analysis tools, modern laboratory techniques, and Geographic Information Systems (GIS). The research concludes that human activities play a major role in the pollution of the Ruandz River. However, when compared to Iraqi and international standards, the physical and chemical parameters of the river’s water pollution do not exceed the acceptable limits.
Keywords: River; Pollution; Water Pollution; Rwandz River